Analysis of Speech Acts in School Radio Broadcast Programs as a Resource for Learning Junior High School Students' Speaking Skills - Rischa Anggraeni Basuki; Suhartono; Abdul Kholiq (LPPM Universitas PGRI Semarang, 2026)
This research explains and describes (1) types of speech acts in school radio broadcast programs; (2) the meaning and intent contained in the speech acts of school radio broadcast programs; (3) The relevance of speech acts in school radio broadcast programs as a source of learning speaking skills for junior high school students. This research uses a qualitative descriptive research type. The results of this research show that speech acts in school radio broadcast programs include locutionary, illocutionary and perlocutionary speech acts. The results of the research conducted show that school radio broadcast programs can be used as a source of learning speaking skills for junior high school students.